A min-max theorem and its applications to nonconservative systems - Li Weiguo; Li Hongjie (International Journal of Mathematics and Mathematical Sciences)
A nonvariational generation of a min-max principle by A. Lazer is made. And it is used to prove a new existence results for a nonconservative systems of ordinary differential equations with resonance.